DONOR SERVICE ORGANIZATION IN DAGESTAN DURING THE GREAT PATRIOTIC WAR - Nagieva, M K (History, Archeology and Ethnography of the Caucasus, 2015)
On the basis of archival sources and special literature the author of the article considers the problem of organization of blood transfusion service in the republic. The article presents the definition of the blood service and the main tasks of the organization. It is noted that the first station of blood transfusion was organized in Makhachkala on the base of the optional clinic of Central Clinical Hospital in 1935. The author highlights some aspects of the activity of Dagestan blood transfusion station during the Great Patriotic War and shows the assistance provided by donors to the wounded who were in evacuation hospitals. The article presents statistical information concerning the percent of blood transfusion from 1941 to 1945 and the main injuries and diseases when blood transfusion was performed in evacuation hospitals, liststhe active donors who were awarded by the badge “Honorary donor of the USSR”. The author notes that developing of scientific questions of blood transfusions both through the country and in our republic continued during the wardespite the difficult military situation. This is evidenced by the fact that 63 reports were devoted to blood transfusionat the first conference of doctors of Dagestan evacuation hospitals that took place in 1941.